AB0357 Impact of Rituximab on Patient-Reported Outcomes in Patients with Rheumatoid Arthritis from The US Corrona Registry. (15th July 2016) - Harrold, L.R.; John, A.; Karki, C.; Li, Y.; Greenberg, J.D.; Kremer, J.M.
Abstract : Background: Patients with rheumatoid arthritis (RA) experience diminished quality of life, including increased disability and RA-related comorbidities. Patient-reported outcomes (PROs) are increasingly being recognized as important measures in determining response to therapy in patients with RA. Objectives: To examine the impact of rituximab on PROs in the Corrona registry, a national US observational cohort of >40, 000 patients with RA. Methods: Between March 1, 2006, and September 1, 2015, patients with RA who had prior exposure to ≥1 tumor necrosis factor inhibitor (TNFi) and newly initiated rituximab while not in remission (Clinical Disease Activity Index [CDAI] >2.8) with a follow-up visit at 1 year (± 3 months) were identified. Changes in PROs, assessed 1 year from baseline and stratified by prior TNFi use, included patient global assessment of disease, pain and fatigue (visual analog score; 0–100); morning stiffness (hours); modified Health Assessment Questionnaire (mHAQ; 0–3) and Euro Quality of Life 5 dimensions questionnaire (EQ-5D). Improvement in EQ-5D domains was defined as patients reporting improvement or resolution of impairment among patients who reported impairment at baseline. Outcomes between the 1 and ≥2 prior TNFi groups were compared using χ 2 or t -tests, as appropriate. Results: Of the 667 patients initiating rituximab included, 284 (43%) had received 1 prior TNFi and 383 (57%) had received ≥2 prior TNFis. Overall, the median (IQR) age was 59 (50–66) years; 79% of patients were female. Baseline mean (SD) CDAI was 25.6 (13.9). Baseline PROs showed that patients were substantially impaired by their disease and were mostly similar between the 1 and ≥2 prior TNFi groups, although patients in the 1 prior TNFi group tended to have longer duration of morning stiffness and greater fatigue scores. At baseline, patients reported median (IQR) global assessment, pain, fatigue and mHAQ scores of 50 (35–73), 60 (31–75), 65 (40–80) and 1 (0.6–1.6), respectively, and a median (IQR) of 1 (0.5–2) hour of morning stiffness. Of the 667 total patients, 63% received rituximab retreatment and persisted on rituximab through 1 year. At 1 year, improvements were reported in all PROs with no significant difference between patients with 1 or ≥2 prior TNFis. Median (IQR) improvements in patient global assessment, pain and fatigue were 7 (−10 to 25), 7 (−5 to 25) and 9 (−5 to 20), respectively. Improvement in EQ-5D categories is shown (Figure ). 51.7% of patients reported no improvement in morning stiffness, 28.5% reported improvement of 1–60 minutes and 19.8% reported improvement of >60 minutes. Conclusions: Real-world data showed that quality of life in this cohort of patients with long-standing, refractory RA was substantially impacted by the disease. One year after initiation of rituximab, improvements were reported in all PROs, such as self-care and usual activities, and were similar between patients with exposure to 1 or ≥2 prior TNFis. Acknowledgement: This study is sponsored by Corrona, LLC. The Corrona RA registry has been supported through contracted subscriptions in the last 2 years by AbbVie, Amgen, AstraZeneca, Bristol-Myers Squibb, Genentech, Horizon Pharma USA, Janssen, Eli Lilly, Novartis, Pfizer and UCB. Disclosure of Interest: L. Harrold Grant/research support from: Corrona, LLC, Employee of: Corrona, LLC, A. John Employee of: Genentech, Inc., C. Karki Employee of: Corrona, LLC, Y. Li: None declared, J. Greenberg Shareholder of: Corrona, LLC, Consultant for: AstraZeneca, Celgene, Novartis and Pfizer, Employee of: Corrona, LLC, J. Kremer Shareholder of: Corrona, LLC, Grant/research support from: Genentech, Inc., Consultant for: Genentech, Inc., Employee of: Corrona, LLC